28 Percutaneous mitral valve repair with mitraclip device in hemodynamically unstable patients: a systematic review. (30th September 2020) - McInerney, A; Martinez-Gomez, E; Triado-Contre, G; Nombela-Franco, L
Abstract : Background: Percutaneous mitral valve edge-to-edge repair (PMVr) with the MitraClip device has been reserved as an alternative treatment for chronic mitral regurgitation (MR) in high surgical risk patients. Acute significant MR has been reported to complicate 12% of myocardial infarctions and is present in 5 to 12% of patients in cardiogenic shock. The use of MitraClip in hemodynamically unstable patients, who are of high surgical risk, is therefore increasing. However, there is a paucity of specific outcome data in this important clinical setting as these patients are generally not included in clinical trials. Objectives: The aim of the present study was to perform a systematic review of published data, and provide further insight into the baseline characteristics, management and clinical outcomes of unstable patients undergoing PMVr with MitraClip. Methods: We conducted a systematic review of the published data on MitraClip from its first use in 2003 to February 2020. Pubmed search terms included 'Acute' and 'MitraClip', and later 'MitraClip' and 'cardiogenic shock'. Studies referring to critically ill patients in cardiogenic shock or acute pulmonary edema were included. Studies referring to stable patients were excluded. Results: A total of 27 publications including 155 patients with significant MR (grade 4 in 91%) were included. Mean age was 70±12 years with median Euroscore II and STS of 15.7 (IQR 10.5–27.6) and 18.1 (IQR 7.6–23.9), respectively. Clinical presentation was with cardiogenic shock in 77.5% of patients. The most frequent etiology of MR was ischemia (77%). Median time between hospital admission and MitraClip implantation was 22 (IQR 8–45) days. Hemodynamic support was required in the majority of the patients (87.1%), with vasoactive drugs and ventricular support in 101 patients (65.2%) and 67 patients (43.2%), respectively. MR was quantified as severe (grade 4) in 91.3% of the patients, with 15.9% related to a papillary muscle rupture in the context of acute STEMI. Left ventricular ejection fraction (LVEF) was moderate-to-severely depressed (34.2 ± 15.6%). Device success was achieved in 147 (95%) patients with a significant reduction in MR (grade≤2 in 94%, p<0.001). The weaning time from the procedure, to discontinuation of circulatory or respiratory support, was 2.5 (IQR 1.0–6.8) days, with an in-hospital mortality and non-fatal complication rate of 9% and 5.2%, respectively. At 6-month follow-up, mortality rate was 21.5%, with persistent reduction in MR severity for survivors (grade≤2 in 83%) and one case of mitral valve reintervention. Conclusions: Percutaneous mitral valve repair with MitraClip device is a safe and viable management option in high-risk patients with cardiogenic shock or refractory pulmonary edema and concomitant moderate-severe MR. Prospective trials are required to confirm these findings, and definitively determine the value of MitraClip in hemodynamically unstable patients.